ANALISIS DAMPAK POSITIF MEDIA SMART HAFIDZ PADA PEMEROLEHAN BAHASA ANAK USIA 2 TAHUN 6 BULAN (STUDI KASUS PADA NIZAM ABQORY AKHYAR) - Arifin, Yusriani; Syamsuri, Andi Sukri; Madeamin, Rosmini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Analysis of the Positive Impact of Smart Hafidz media on the Language Acquisition of Children 2 Years 6 Months (Case Study of Nizam Abqory Akhyar). This research aims to reveal an analysis of the positive impact of Smart Hafidz media on the language acquisition of children aged 2 years 6 months. With a research subject named Nizam Abqory Akhyar, focusing on the study of sound sounds or the phonology of vowels and consonants. The aim is to see how far Nizam's children have developed in the phonological aspect in acquiring language. This type of research is qualitative research. With the case study method. This research was carried out by analyzing language acquisition with data in the form of songs, prayers and films as well as conversations between Nizam and his family at home from watching Smart Hafidz. Smart Hafidz is the right media to give to children to avoid negative viewing. This research uses media in the form of video recordings and notes with the vocabulary spoken by a 2 year 6 month old boy named Nizam. By collecting data in the form of observation, video recording, listening techniques and note-taking techniques. As well as data analysis techniques using data reduction techniques, data presentation, conclusions or verification, as well as describing all phonological aspects and then explaining them. Data findings from research show that Smart Hafidz has a positive impact on Nizam's language acquisition, such as very clear pronunciation of phonemes or articulation, vowels /a/, /i/, /u/, /e/, /o/, /e'/ and consonants /b/, /c/, /d/, /f/, /g/, /h/, /j/, /k/, /l/, /m/, /n/, /p/, / s/, /t/, /v/, /w/, /y/, /z/. and often asks about vocabulary that he has just listened to or watched on Smart Hafidz media.